Cancer care for Ukrainian refugees: Strategic impact assessments in the early days of the conflict. (December 2022) - Van Hemelrijck, M.; Fox, L.; Beyer, K.; Fedaraviciute, E.; George, G.; Hadi, H.; Haire, A.; Handford, J.; Mera, A.; Monroy-Iglesias, M.J.; Moss, C.L.; Perdek, N.; et al.
Abstract: Background: The invasion of Ukraine by Russia in February 2022 has resulted in destruction of healthcare infrastructure and triggered the largest wave of internally displaced populations and refugees since World War Two. Conflicts in transitioned countries such as Ukraine create new non-communicable disease (NCD) challenges, especially for cancer care for refugees and humanitarian assistance in host countries. In the early days, rapid attempts were made to model possible impacts. Methods: By evaluating open source intelligence used in the first three months of the conflict through snowball search methods, we aimed to address: (i) burden of cancer in Ukrainian population, specifically considering translating to the refugees population, and its cancer care capacity; ii) baseline capacity/strengths of cancer systems in initial host countries. Moreover, using a baseline scenario based on crude cancer incidence in Ukraine, and considering data from UNHCR, we estimated how cancer cases would be distributed across host countries. Finally, a surveillance assessment instrument was created, intersecting health system's capacity and influx of internally displaced populations and refugees. Findings and conclusions: The total new cancer patients per month in pre-conflict Ukraine was estimated as 13, 106, of which < 1 % are paediatric cases. The estimated cancer cases in the refugee population (combining prevalent and incident), assuming 7.5 million refugees by July 2022 and a female:male ratio of 9:1, was 33, 121 individuals (Poland: 19284; Hungary: 3484; Moldova: 2651; Slovakia: 2421; Romania: 5281). According to our assessments, Poland is the only neighbouring country classified as green/yellow for cancer capacity, i.e. sufficient ablility to absorb additional burden into national health system; Slovakia we graded as yellow, Hungary and Romania as yellow/red and Moldova as red. Highlights: Our estimate is that 60–70 % of cancer care has been disrupted in the first month of fighting, which will increase to 90 % in four months at current trajectories for the 13–14 M million citizens living in conflict impacted regions (even those from which Russian forces have now withdrawn). The impact in terms of delays in diagnosis and treatment is cumulative and massive. Whilst we estimated that there would be about 33, 000 cancer patients in these host countries, the actual number presenting for treatment is likely to be much lower; many will succumb to their disease (end stage), whilst others will not present until there are acute emergencies. It is not possible at this stage to give reliable estimates. Although Poland will receive the majority of these, the impact of even the more modest numbers on other host countries will impose a significant burden. Our estimate is that the carrying capacity for initial host countries to manage projected volumes of cancer patients is moderate to weak. Current sentiment analysis and policy reactions by host countries is estimated as good, with high confidence. However, this needs to be continually evaluated through segmented analysis to understand how cancer care for refugees is being perceived by host countries. Our analysis reflects the reality that Ukraine and Europe are now experiencing their first cancer (and NCD) humanitarian crisis. As structures and organisations begin to focus on gathering actionable intelligence, it is essential not to lose sight of the universal declaration of human rights, which guarantees care irrespective of status and ability to pay.